The Effectiveness of Cognitive Conflict-Based Learning Models Using Interactive Multimedia - Nadia Zuwita; Fatni Mufit (Universitas Negeri Padang, 2023)
The cognitive conflict learning model can be used to improve student understanding of concepts, 21st century developments demand IT-assisted learning. Several studies have shown that understanding of physics concepts is low resulting in misconceptions, one of which is sound and light waves. The solution to these problems is integration using cognitive conflict-based learning models assisted by interactive multimedia. Interactive multimedia is a system for implementing cognitive conflict-based learning models, because it has the same goal of increasing students' conceptual understanding. Cognitive conflict-based learning models can improve students' conceptual understanding and remediate misconceptions because they have 4 skills, namely preconception and misconception activities, presentation of cognitive conflicts, discovery and concept similarities, and reflection. The purpose of this study was to analyze the effectiveness of cognitive conflict-based learning models on students' understanding of the concept of sound and light waves. This study used an experimental method with a quasi-experimental type. The sample consisted of 65 high school students with two sample classes namely the experimental class and the first control class which were selected by purposive random sampling technique. The instrument in this study was a valid concept, the data were obtained with the help of IBM SPSS 20 statistics, the results obtained were sig.asim < 0.05 which is included in the Ho rejection area, that cognitive conflict-based learning models affect students' conceptual understanding of sound and light waves Thus, the cognitive conflict-based learning model assisted by interactive multimedia is effective for use in remediating misconceptions and increasing students' conceptual understanding.